2017
DOI: 10.1111/evo.13310
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection on spontaneous mutations strengthens the between‐sex genetic correlation for fitness

Abstract: A proposed benefit to sexual selection is that it promotes purging of deleterious mutations from populations. For this benefit to be realized, sexual selection, which is usually stronger on males, must purge mutations deleterious to both sexes. Here, we experimentally test the hypothesis that sexual selection on males purges deleterious mutations that affect both male and female fitness. We measured male and female fitness in two panels of spontaneous mutation-accumulation lines of the fly, Drosophila serrata,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…In a mutation accumulation study with D. serrata , sexual selection did not prevent fitness reductions associated with the buildup of load, but did strengthen the fitness correlation between males and females, indicating an importance for sex‐limited genetic load for population fitness (Allen et al. ). Evidence that sexual selection helps to fix beneficial alleles more effectively when environments change also varies, with some studies reporting that sexual selection improves adaptation to a novel environment (Fricke and Arnqvist ), aids the evolution of pesticide resistance (Jacomb et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a mutation accumulation study with D. serrata , sexual selection did not prevent fitness reductions associated with the buildup of load, but did strengthen the fitness correlation between males and females, indicating an importance for sex‐limited genetic load for population fitness (Allen et al. ). Evidence that sexual selection helps to fix beneficial alleles more effectively when environments change also varies, with some studies reporting that sexual selection improves adaptation to a novel environment (Fricke and Arnqvist ), aids the evolution of pesticide resistance (Jacomb et al.…”
Section: Discussionmentioning
confidence: 99%
“…This may at first appear as if our manipulation of genetic quality had a larger influence on condition in males. Instead, we attribute this larger difference in males to them experiencing stronger sexual selection-a compelling argument, as this effect is believed to be behind the stronger selection against deleterious mutations commonly observed in males compared to females (Whitlock and Agrawal 2009;Sharp and Agrawal 2013;Grieshop et al 2016; but see Allen et al 2017;Prokop et al 2017). An alternative explanation for this pattern is that D. melanogaster males have more sex-limited transcripts than do females overall, as the testes are particularly enriched for sex-limited gene expression (Graveley et al 2011).…”
Section: Genetic Quality and Sex-specific Aging 767mentioning
confidence: 92%
“…In contrast, studies in Tribolium castaneum and Anopheles gambiae [13] [14] have shown that many of the sex-biased genes in these species are female biased. In general, male-biased genes evolve more rapidly than female-biased genes [15] [16] [17] [18], suggesting that males experience stronger positive selection than females [4][5], although the genetic architecture of gene expression and other factors might also explain the more rapid evolution of male-biased genes [19]. Sex-biased gene expression has been documented in a range of different species, including brown algae [20], birds [21] [22], nematodes [23], Daphnia pulex [10], cichlid shes [24], guppies [25], moths [26], the pea aphid [27], and multiple insect species [8] [33].…”
Section: Introductionmentioning
confidence: 99%